Chemical Composition of Gum Mastic Quality of Natural Pistacia Species Plants of Turkey - BOZTOK, SENOL; COKUYSAL, BURCIN (Asian Journal of Chemistry, 2010)
In this study, the mastic, leaf and fruit samples from cultivated Pistacia lentiscus L. varieties, pruned naturally grown bush forms of Pistacia lentiscus and Pistacia atlantica were examined. The samples were collected from different locations between August and September and distilled with a Clevenger device. By GC/MS analysis, the essential oil components were determined. The essential oil components of the· mastics from the Aegean coast belt of Turkey and the mastics from Chios Island of Greece, the unique producer of mastic, have similar characteristics.